Seasonal Water Temperature Variability of Springs From Porous Sediments in Gryżynka Valley, Western Poland - Szczucińska, Anna Maria; Wasielewski, Hieronim (Quaestiones Geographicae, 2013)
This paper discusses fluctuations in spring water temperature and its correlation to climate and aquifer characteristics. Data from nine springs in the Gryżynka River catchment (Polish Plain) were taken monthly (November 2005 to October 2010). The springs examined in this study are characterised by significant thermal inertia in contrast to air temperature, that is expressed in small temperature amplitudes that range from 1.3°C to 2.3°C. The average temperature of the springs is about 9°C. The research proved that observed groundwater temperature variations on the surface resulted mainly from atmospheric conditions, especially air temperature. The highest water temperatures (up to 10°C) were observed during late summer and early autumn, and the lowest temperature (7.7°C) was observed at the end of the winter period. The range of spring water temperature variability may reflect amount of water contribution from local water recharge in the spring vicinity.